2018
DOI: 10.15520/ijcrr/2018/9/02/428
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effect of Alcoholic Extract of Nigella sativa L on Bovine Fibroblast-like synoviocyte and THP-1

Abstract: Due to the side effects of current therapies for osteoarthritis one of the alternative medicine is using herbal medicine such as Nigella sativa .L which in Iranian traditional medicine has been used as a treatment option. The purpose of this study is evaluating the effect of alcoholic extract of Nigella sativa (AENS) on pro-inflammatory cytokines in Bovine Fibroblast-like BFLs (BFLS) and THP-1. BFLS cells were isolated from Radiocarpal joint. After evaluating of LC50 (27 µg/mL), both cells (5x105 (cells\wel)) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…N. sativa oil extract has also been shown to reduce the expression of pro‐inflammatory cytokines cyclooxygenase‐2 (COX2), inducible nitric oxide synthetase, tumour necrosis factor‐α (TNF‐α), prostaglandin (PG)‐E2 and lipoxygenase released by activated inflammatory and/or damaged host cells within an inflamed joint and hence could be useful in the treatment of osteoarthritis and rheumatoid arthritis 10,32 33 …”
Section: Pharmacological Activity Of N Sativa and Tqmentioning
confidence: 99%
“…N. sativa oil extract has also been shown to reduce the expression of pro‐inflammatory cytokines cyclooxygenase‐2 (COX2), inducible nitric oxide synthetase, tumour necrosis factor‐α (TNF‐α), prostaglandin (PG)‐E2 and lipoxygenase released by activated inflammatory and/or damaged host cells within an inflamed joint and hence could be useful in the treatment of osteoarthritis and rheumatoid arthritis 10,32 33 …”
Section: Pharmacological Activity Of N Sativa and Tqmentioning
confidence: 99%
“…This mediator activates cells from the tissue that are followed by the release of metalloproteinase which causes pain or inflammation. Tumor necrosis factor (TNF) α is considered to be the main inflammatory mediator [24]. The number of leukocytes in granuloma pouch (Table 3) showed that the lowest leukocyte count was obtained in the hydrocortisone 2.5% group followed by NB 10%, 7.5% and 5% respectively.…”
Section: Discussionmentioning
confidence: 99%